Rise of cholera in Iraq: A rising concern. (September 2022) - Qamar, Khulud; Malik, Umer Usman; Yousuf, Juvairia; Essar, Mohammad Yasir; Muzzamil, Muhammad; Hashim, Hashim Talib; Shah, Jaffer
Abstract: With over seven pandemics and four million reported cases, Cholera remains of the most prevalent acute watery diarrheal diseases in the world to date. As in other developing countries, Iraq once again combats Cholera – and its past encounter in 2015, where the death toll reached 1500, highlights the importance of quickly addressing the current outbreak. The war-torn state of the nation, malnourished public, lack of sanitation and hygiene, mass displacement and global warming all contribute to the prevalence of Cholera in Iraq. Along with the current efforts, additional strategies are recommended for managing cholera cases, such as awareness campaigns, monitoring the safety of water bodies, and food inspection.